Microwave Photonic Phase Shifter with frequency up-/down-conversion. (May 2020) - Chen, Dou; Ma, Jianxin
Abstract: In this paper, we propose a microwave photonic phase shifter with frequency conversion (MPSFC) without optically filtering to realize both frequency up- and down-conversion and a full 360º phase-shift for the microwave signal based on an integrated dual-polarization dual-parallel Mach-Zehnder modulator (DP-DPMZM). As the radio frequency (RF) signal is frequency down-converted to intermediate frequency (IF) signal or the IF signal can be frequency up-converted to RF signal, the phase of the output IF or RF signals can be shifted by adjusting the DC bias voltage of PolM. Simulation results demonstrate that both 360º continuously tunable phase shift and frequency conversion can be implemented simultaneously.